Quantifying the impact of patient boarding on emergency department length of stay: All admitted patients are negatively affected by boarding - Leslie A. Laam; Andrea A. Wary; Ronald S. Strony; Michael H. Fitzpatrick; Chadd K. Kraus (Journal of the American College of Emergency Physicians Open, 2021)
Abstract Background Patients boarding in the emergency department (ED) as a result of delays in bed placement are associated with increased morbidity and mortality. Prior literature on ED boarding does not explore the impact of boarding on patients admitted to the hospital from the ED. The objective of this study was to evaluate the impact of patient boarding on ED length of stay for all patients admitted to the hospital. Methods This was an institutional review board–approved, retrospective review of all patients from January 1, 2015, through June 30, 2019, presenting to 2 large EDs in a single health system in Pennsylvania. Quantile regression models were created to estimate the impact of patients boarding in the ED on length of stay for all ED patients admitted to the hospital. Results A total number of 466,449 ED encounters were analyzed across two EDs. At one ED, for every patient boarded, the median ED length of stay for all admitted patients increased by 14.0 minutes (P < 0.001). At the second ED, for every patient boarded in the ED, the median ED length of stay increased by 12.4 minutes (P < 0.001). Conclusion ED boarding impacts length of stay for all patients admitted through the ED and not just those admitted patients who are boarded. This study provides an estimate for the increased ED length of stay experienced by all patients admitted to the hospital as a function of patient boarding.